Factors Influencing Length of Stay and Discharge Destination of Patients with Hip Fracture Rehabilitating in a Private Care Setting - Zoe Thornburgh; Dinesh Samuel (Geriatrics, 2022)
Background: Rehabilitation after a hip fracture has long-term importance, prompting some patients to utilise private services. Insufficient data regarding private rehabilitation in the UK can cause ambiguity and potential problems for all involved. Aim: The present study, involving patients with hip fractures rehabilitating in a private UK care setting, examined relationships between length of stay (LoS), discharge destination (DD) and 12 predictor variables. Methods: The variables included the retrospective measurement of the Functional Independence Measure. The variables were informed by a literature review and patient and public involvement. Retrospective data from the records of patients with hip fractures were utilised. Data were analysed using Spearman’s rho, Mann–Whitney U, Kruskal–Wallis H and chi-squared tests as appropriate. Odds ratios, distribution quartiles and survivor analysis were also utilised. Results: The median length of stay (LoS) was 20.5 days: 82% returned home, 6.5% died and 11.5% remained as long-term residents. Significant relationships existed between LoS and age (p = 0.004), comorbidities (p = 0.001) and FIMadmission (p = 0.001). DD was associated with age (p = 0.007), delirium (p = 0.018), comorbidities (p = 0.001) and both FIMpre-fracture and FIMadmission (p = 0.000). Conclusions: Factors associated with length of stay were identified, but further research incorporating multiple sites is required for greater predictor precision. Discharge destination was evident by 90 days, facilitating long-term planning.